Legal basis land protection from contamination and spoilage - Лисанець, О. С. (Theory and practice of jurisprudence, 2016)
Problem setting. The current state of Ukrainian society is characterized by increasing pressure on land resources and therefore threatens to become a danger to itself .. One of the negative factors affecting the quality of the land is state of anthropogenic pollution and damage, leading to an imbalance both in the nature, and adversely affect the life and health of the person, directly or indirectly through the environment. The above is the need to address issues of land. The situation that has developed with the protection of land from pollution and defacement, needed and requires effective enforcement measures, including legal matters. Proof of this is the fact that there has been contaminated area covering 15% of the country, and polluted and very polluted, where the living conditions of the population has worsened and stretched, are respectively about 40% and 30% of the state, 17% of experiencing flooding, more than 18 % exposed to erosion. Recent research and publications analysis. The study of some issues concerning the quality of the land in Ukraine has always paid attention to an important and comprehensive. They were devoted to a number of significant monographs and dissertations, numerous scientific articles. Important contribution to the legal protection of land made by such scholars as V. Andreytseva [1], S. Baluk [2], N.S. Gavrish [3], O.V. Konysheva [4] P.F. Kulinich [5] and others. In their writings thoroughly analyzed the important legal aspects of land with important theoretical and practical significance for the protection of land in Ukraine. 2 Paper objective. The severity of the problems that have been established for the protection of land in Ukraine against pollution and deterioration, an urgent need to resolve them require effective enforcement measures, including legal matters. The purpose of this paper is to study the legal principles of land protection from contamination and spoilage. Paper main body. Legislator has clearly outlined the range of possible contaminants earth, their harm and danger and property pollute the soil of the earth, which is typical for certain types of substances, agents and materials that may be present in safe substances and materials. The danger of such substances and materials depends on the objective circumstances, the concentration of pollutants, the previous state of the soil layer, the socio-economic importance of appropriate land and so on. We must recognize that with all the specific conditions of the actual pollution or deterioration of land may be any, existing contaminants, agents and materials that function independently or are part of other subjects and are harmful to people or the environment. So, in fact possible contamination of land by any contaminants. Conclusions of the research. Important areas of legal protection of land from pollution to contamination should be accounting Wastes and their certification, systematic monitoring of natural resources. For timely response to identified cases of gradual pollution and deterioration of land in Ukraine to use these ecological expertise, survey and forecasting further development of adverse events in health states. Although a large number of legal acts regulating social relations in terms of the national land reform, land legislation is imperfect and needs improvement. Moreover, the process of reform of land relations incomplete, especially in the areas of land. Therefore, further studies are needed positive foreign land management practices, in particular European countries.